Teaching from Home? Now What? Preparing Your Online Emergency Teaching Toolkit. Issue 6 (23rd July 2020) - Brooks, Collin; Mosier, Brian; Bassett, Matthew
Abstract: The purpose of this article is to develop a physical education teachers' emergency virtual toolkit in the case that a crisis takes away the opportunity to instruct students in person within a future event. Specifically, this article will discuss how a physical educator can use social media and professional groups to access resources, navigate learning management systems, share their resources, and practice self-care during a crisis.